2022
DOI: 10.3389/fphar.2022.808460
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Efficacy of Curcumin as an Adjunct to Non-Surgical Periodontal Treatment: A Systematic Review and Meta-Analysis

Abstract: Objective: Curcumin has been used as an adjunct to non-surgical periodontal treatment. However, the efficacy of curcumin in the periodontal therapy remained controversial. This study aimed to evaluate the anti-inflammatory efficacy of curcumin as an adjunct to non-surgical periodontal treatment (NPT) by systematic review.Methods: Databases including Embase, PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), and ClinicalTrials.gov were searched to identify relevant RCTs on the use of curcumin as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Although in many systems, curcumin will be rapidly metabolised to the less active form THC3, in the oral cavity, it may have a role to play in reducing the exaggerated inflammatory burden evident within periodontal diseases, via topical application to gingival tissues. Clinical trials in this area have begun 58 and a meta‐analysis of the use of curcumin as a nonsurgical periodontal treatment has reported that curcumin can decrease gingival index, sulcus bleeding index but not bleeding on probing 59 . In conclusion, we have shown that curcumin can decrease inflammatory markers produced by an oral epithelial cell line in response to challenge by F. nucleatum .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Although in many systems, curcumin will be rapidly metabolised to the less active form THC3, in the oral cavity, it may have a role to play in reducing the exaggerated inflammatory burden evident within periodontal diseases, via topical application to gingival tissues. Clinical trials in this area have begun 58 and a meta‐analysis of the use of curcumin as a nonsurgical periodontal treatment has reported that curcumin can decrease gingival index, sulcus bleeding index but not bleeding on probing 59 . In conclusion, we have shown that curcumin can decrease inflammatory markers produced by an oral epithelial cell line in response to challenge by F. nucleatum .…”
Section: Discussionmentioning
confidence: 61%
“…Clinical trials in this area have begun 58 and a meta-analysis of the use of curcumin as a nonsurgical periodontal treatment has reported that curcumin can decrease gingival index, sulcus bleeding index but not bleeding on probing. 59 In conclusion, we have shown that curcumin can decrease inflammatory markers produced by an oral epithelial cell line in response to challenge by F. nucleatum. The mechanism by which this occurs appears to be driven by the induction of NrF2 responses.…”
Section: Discussionmentioning
confidence: 67%
“…We aimed to include all types of study protocols including SRP, SPD and no treatment in order to accumulate the available evidence in a single publication. A recent study that examined the anti-inflammatory efficacy of curcumin as an adjunct to non-surgical periodontal treatment included 18 randomized clinical trials and demonstrated significant reduction in gingival index and sulcus bleeding index when compared to non-surgical treatment alone [ 74 ]. When curcumin was compared to CHX as adjunct to SRP, it showed similar reductions of PPD, CAL, gingival index and plaque index with CHX [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is a result of the strong antimicrobial activity of these herbal products and their synergistic effect again oral biofilm. Herbs may also inhibit the growth of periodontal pathogens, reduce the inflammatory response of the host to the bacteria and finally inhibit innate and adaptive immune responses in periodontal tissues [ 74 ]. For example, the use of Salvadora persica extract has significant anti-streptococcal and anti-lactobacilli effects and is associated with a significant reduction in plaque score and cariogenic bacterial count [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, over the past 50 years, Curcumin in an ingredient within multiple natural extracts used in traditional medicine across half of Asia. Curcumin has been recommended as adjunctive treatment to non-surgical periodontal therapy in periodontitis, but its molecular mechanism remains a mystery [9]. Therefore, in the present study, we aimed to integrate singlecell analysis with bulk transcriptome to unravel the secrets behind it.…”
Section: Introductionmentioning
confidence: 99%